Association of ABO and Rh Blood Group in Susceptibility, Severity, and Mortality of Coronavirus Disease 2019: A Hospital-Based Study From Delhi, India - Rana, Rashmi; Ranjan, Vivek; Kumar, Naveen (Frontiers in Cellular and Infection Microbiology, 2021)
Background: ABO as well as Rh blood group systems are associated with many diseases including cancerous, infectious, non-infectious, bacterial as well as viral diseases. Studies have shown association of blood groups A and O with higher and lower odds for coronavirus disease 2019 positivity respectively. Methods: This is a single centre, retrospective study conducted at Sir Ganga Ram Hospital, Delhi. We investigated the association of ABO and Rh blood groups with susceptibility to coronavirus disease 2019 infection, severity of disease, recovery period and mortality of patients. Patients were enrolled from 8 April 2020 to 4 October 2020. 2586 RT-PCR confirmed COVID-19 patients were recruited. Data was analysed using chi square test, odds ratio and Mann-Whitney test to determine the association of blood groups. Results: In the 2586 COVID-19 infected patients, the frequencies of A, B, O and AB were 29.93%, 41.80%, 21.19% and 7.98% percent respectively. 98.07% of the patients were Rh positive. Blood group A (odds ratio: 1.53, CI: 1.40-1.66, p <0.001) and B (odds ratio: 1.15, CI: 1.06-1.24, p <0.001) is observed to be significantly associated with COVID-19 susceptibility, whereas blood group O (odds ratio: 0.65, CI: 0.59-0.71, p <0.001) and AB (odds ratio: 0.66, CI: 0.59-0.71, p <0.001) have low risk of COVID-19 infection. Conclusion: A, B and Rh+ are found to be more susceptible to COVID-19 infection, whereas blood group O, AB and Rh- are at a lower risk of COVID-19 infection. No association was found between blood groups and susceptibility to severity of disease and mortality.